Pola Interaksi dalam Sentra Industri Kecil dan Menengah (IKM) - Faizal Ahmad; Muhammad Setiawan Kusmulyono; Agus Wijaya Soehadi (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
Small and medium industrial (SMI) centers are one of the contributors to the national economy performance. Several programs carried out across stakeholders are directed at being able to strengthen SMI centers to become more competitive. Previous research has not described how social interaction patterns emerge in the context of collaboration or conflict in an industrial center. This research was conducted to explore more about patterns of entrepreneurial interaction that occurred in SMI centers in West Java and Central Java. This study uses a qualitative approach by taking informant samples of SMI centers that are typical in 10 regencies and cities. The results of this study are described through several main points of discussion: (1) center institutions and challenges within them, (2) micro partnerships between SMIs, and (3) conflict of interest between craftsmen within the centers.